Pengaruh Leader Member Exchange, Kualitas Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan di Kantor Bpkad Kota Pekalongan - Shofiyuddin, Muhammad; Pranantya (Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this research is to determine the influence of Leader Member Exchange, work quality and organizational culture on employee performance at the Pekalongan City Regional Revenue and Financial Assets Agency Office. This research uses quantitative research methods. The questionnaire data collection technique is by distributing questionnaires to 30 respondents, then carrying out further analysis of the multiple linear regression test data, then carrying out the t test and F test. The results of this research show that Leader Member Exchange has an effect on employee performance, work quality has no effect on employee performance and Organizational Culture influence employee performance, while Leader Member Exchange, Work Quality and Organizational Culture simultaneously influence employee performance.